Ancient species offers contemporary therapeutics: an update on shark VNAR single domain antibody sequences, phage libraries and potential clinical applications. (21st January 2020) - English, Hejiao; Hong, Jessica; Ho, Mitchell
ABSTRACT: The antigen binding variable domain (VNAR ) of the shark immunoglobulin new antigen receptor (IgNAR) evolved approximately 500 million years ago and it is one of the smallest antibody fragments in the animal kingdom with sizes of 12–15 kDa. This review discusses the current knowledge of the shark VNAR single domain sequences and ongoing development of shark VNAR s as research tools as well as potential therapeutics, in particular highlighting the recent next-generation sequencing analysis of 1.2 million shark VNAR sequences and construction of a large phage displayed shark VNAR library from six naïve adult nurse sharks ( Ginglymostoma cirratum ). The large phage-displayed VNAR single domain library covers all the four known VNAR types (Types I–IV) and many previously unknown types. Ongoing preclinical development will help define the utility of shark VNAR single domains as a potentially new family of drug candidates for treating cancer and other human diseases.